CHEAPER DEPRECIATION. - Taggart, H. F. (The Accounting Review, 1926)
Abstract In spite of all that has been written in recent years with regard to depreciation, confusion still persists. A fairly recent article attempts to prove that owners of buildings are cheating themselves by charging depreciation at too high rates. Rates of two to five percent, varying according to the type of construction and other conditions, are too high, the writer argues, not because buildings of these types last, on the average, longer than the corresponding number of years, but, forsooth, because an annuity of the amount of the annual charges produced by using these rates will, when properly invested, amount to a greater sum than the cost of the building by the end of the given length of life. For example, $50,000 building whose estimated life is fifty years will give rise each year to a charge to depreciation of $1,000 on the straight-line method. An annuity of this amount invested at 5% will amount to no less than $209,348 in the same length of time. The annuity required to accumulate $50,000 under these conditions is only $238.89. "If the annual depreciation charge is set aside," says the writer, invested in interest-bearing deposits and the interest is annually reinvested, the investment is recovered within a much shorter period.